Differential vulnerability of thalamic nuclei in multiple sclerosis. (February 2023) - Blyau, Simon; Koubiyr, Ismail; Saranathan, Manojkumar; Coupé, Pierrick; Deloire, Mathilde; Charré-Morin, Julie; Saubusse, Aurore; Zhang, Bei; Rutt, Brian; Dousset, Vincent; Brochet, Bruno; Ruet, Aurélie; et al.
Objectives: Investigating differential vulnerability of thalamic nuclei in multiple sclerosis (MS). Methods: In a secondary analysis of prospectively collected datasets, we pooled 136 patients with MS or clinically isolated syndrome and 71 healthy controls all scanned with conventional 3D-T1 and white-matter-nulled magnetization-prepared rapid gradient echo (WMn-MPRAGE) and tested for cognitive performance. T1-based thalamic segmentation was compared with the reference WMn-MPRAGE method. Volumes of thalamic nuclei were compared according to clinical phenotypes and cognitive profile. Results: T1- and WMn-MPRAGE provided comparable segmentations (0.84 ± 0.13 < volume-similarity-index < 0.95 ± 0.03). Medial and posterior thalamic groups were significantly more affected than anterior and lateral groups. Cognitive impairment related to volume loss of the anterior group. Conclusion: Thalamic nuclei closest to the third ventricle are more affected, with cognitive consequences.